Physiological reactivity in response to a fear‐induced virtual reality experience: Associations with psychopathic traits. (21st August 2018) - Thomson, Nicholas D.; Aboutanos, Michel; Kiehl, Kent A.; Neumann, Craig; Galusha, Carla; Fanti, Kostas A.
Abstract: Despite the longstanding discussion around the link between psychopathy and fearlessness, few studies have explicitly tested this association, and results have been mixed. This may be due, in part, to the lack of specificity in fear assessment. Further, the relation between psychopathy and fear may be better understood using the two‐factor model because, in theory, fear has opposing associations with interpersonal‐affective (Factor 1) and impulsive‐antisocial (Factor 2) traits. The present study aimed to test if the two factors of psychopathy are deferentially related to fear reactivity. To examine this, we collected sympathetic (SNS; skin conductance) and parasympathetic (PNS; respiratory sinus arrhythmia) nervous system reactivity to an interactive virtual reality horror video in a nonclinical sample ( N = 103). Also, we included measures of emotional reactivity to fear and self‐report of situational fear. Results indicated that coinhibition (i.e., low PNS and SNS) of the two physiological systems predicted Factor 1, suggesting that individuals high on Factor 1 showed little change in both branches of the autonomic nervous system in response to fear. In contrast, Factor 2 was predicted by high PNS reactivity, suggesting a vulnerability to emotion dysregulation. On emotional reactivity, Factor 1 was related to feeling happier after the fear condition, whereas Factor 2 was related to feeling less in control. Factor 1 was inversely associated with situational fear, specifically, lower scores of social phobias, fear of aggression, and physical injury. In summary, the results provide evidence that psychopathy is related to fearlessness; however, this is unique to the personality features of psychopathy.